PENGARUH PENGELOLAAN PIUTANG DAN ASET TERHADAP KINERJA KEUANGAN PERUSAHAAN PT TEMAS SHIPPING PERIODE 2017-2021 - Oktaviana, Vina; Sitorus, Eduward Tony; Dameria Napitupulu, Rina (Jurnal Manajemen, Akuntansi, Ekonomi, 2022)
This study aims to determine the effect of receivables and asset turnover on the financial performance of the company PT. Temas Shipping period 2017-2021 in quarterly.The source of this research uses secondary data. The type of research used is quantitative research with descriptive analysis and multiple linear regression analysis measured using SPSS 25.00. This research data collection uses documentation. The sample of this research is 5 periods of financial statements at PT. Temas Shipping by using the non-probability sampling method, namely the saturated sample, the population is the same as the sample.The results of this study indicate that the management of receivables at PT. Temas Shipping ranges between 3.10 times and 11.50 times with an average value of 7.76 times. Asset management at PT. Temas Shipping ranged between 34.38% and 102.91% with an average value of 49.08%. The Company's performance at PT Temas Shipping is between (3.61)% and 84.32% with an average value of 15.92%. The results of hypothesis testing indicate that Receivable Management has a positive and significant effect on Financial Performance (ROA), while Asset Management has a positive and significant effect on Financial Performance (ROA).Meanwhile, simultaneously, Receivable Management and Asset Management have a positive and significant effect. R square value of 0.818 which indicates 81.8% ROA can be explained by the independent variable, while the remaining 18.2% is explained outside of other variables outside this study.